THE IMPACT OF ANTENATAL HEALTH EDUCATION ON HEALTHY PREGNANCY AND SAFE DELIVERY - Atmita Mei Riatna Gultom (International Journal Labs, 2024)
Pregnancy is an important period for a woman. During this period, women experience many physical and emotional changes that require special attention and care. Antenatal health education is an effort to provide knowledge and information to pregnant women about pregnancy, childbirth and postpartum health. The aim of this research is to determine the impact of antenatal health education on healthy pregnancies and safe births. This study used qualitative research methods. Research data was obtained through literature study and in-depth interviews with 10 pregnant women who had attended antenatal health education. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that antenatal health education has a positive impact on healthy pregnancies and safe births. Pregnant women who take part in antenatal health education have better knowledge about pregnancy, childbirth and postpartum health. This knowledge helps pregnant women to take better care of themselves and their fetus' health, make the right decisions regarding pregnancy and childbirth, prepare themselves physically and mentally for labor and postpartum, and face pregnancy and childbirth complications more calmly.